The retrogressive thaw slump (RTS) inventory in permafrost region of the QTP - Luo Jing; Niu Fujun; Lin Zhanju; Liu Minghao; Yin Guoan; Gao Zeyong (Zenodo, 2022)
This dataset containthe retrogressive thaw slump (RTS) inventory in permafrost region of the Qinghai–Tibet Plateau (QTP)based on field investigations and the manual interpretation of the Gaofen-1 and Gaofen-2 images.RTSs were visually detected based on the presence of recently exposed sediments, poorly developed vegetation, and distinct headwalls. To avoid misdelineation of the RTS, the entire permafrost region of the QTP was divided into a large number of grids measuring 5 × 5 km each. Grids with slope degrees below 1° or higher than 15° were excluded because RTSs are rarely found at these slopes according to our previous study and field investigations. RTSs in the remaining grids were detected and sketched by the first author and then examined by at least two other experienced authors. Once a RTS was identified, it was assigned a unique number and classified based on its initiation such as next to a river (R), by lake erosion (L), and after the occurrence of active-layer detachment slide.